Features of Interactional Styles Used by Toru Muranishi in The Naked Director Series - Andrew William Ray; Nani Indrajani Tjitrakusuma (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study focuses on analyzing the features of interactional style used by a character in the Netflix TV series. This study aims to find the features of interactional style used by Toru as the main character of The Naked Director Netflix series on business topics and in what business contexts Toru uses the features of interactional styles. The writers used the theory of interactional styles by Holmes (2006). This study employed a qualitative approach. This study showed that Toru used both feminine and masculine interactional styles in The Naked Director Netflix series. Toru also used different kinds of interactional style features in different business contexts. Toru used feminine interactional style features mostly when talking to people with similar power and authority to his and used masculine features of interactional style when he was talking to people who have lower authority and power than his.